(untitled) (Veterinary Science, 2025)
Urinary obstruction in canines, typically associated with urolithiasis, can have unusual etiologies, such as the migration of foreign bodies. We present the case of a castrated male canine with recurrent urethral obstruction. Plain and contrast radiographic studies revealed the presence of an intraurethral projectile. Successful retrograde hydropropulsion was performed, followed by surgical removal of the foreign body. It is presumed that the delayed migration of the projectile was due to the combination of body movements and progressive tissue erosion, allowing its displacement to the urethra. This case highlights the importance of considering atypical etiologies in cases of recurrent urinary obstruction and emphasizes the diagnostic value of imaging. Retrograde hydropropulsion proved to be an effective tool in the initial resolution of the condition. The similarity to cases described in human medicine reinforces the need to include the migration of foreign bodies as a differential diagnosis in patients with urinary obstruction, contributing to the knowledge of infrequent causes in veterinary medicine.